Anti-IL-17/23 Drugs for the Treatment of Moderate-to-Severe Hidradenitis Suppurativa in Patients With Concomitant Psoriasis: A Multicenter Retrospective Study - Gargiulo, Luigi; Ibba, Luciano; Narcisi, Alessandra; Giordano, Silvia; Maronese, Carlo A.; Martora, Fabrizio; Repetto, Federica; Paolino, Giovanni; Balato, Anna; Burlando, Martina; Dapavo, Paolo; Dini, Valentina; et al. (Dermatology Practical & Conceptual, 2024)
Introduction: Psoriasis and hidradenitis suppurativa (HS) are chronic inflammatory diseases with significant overlap in their immunologic pathways, which involve cytokines such as tumor necrosis factor-alfa, interleukin (IL)-17, and IL-23. Current treatment options for HS are limited, as only adalimumab and secukinumab are approved for severe cases. Given the overlapping pathogenetic features between HS and psoriasis, anti-IL-17 and anti-IL-23 drugs could represent valuable treatments for the management of HS. Objectives: We sought to evaluate the effectiveness and safety of anti-IL-17 and anti-IL-23 drugs in patients with HS and concomitant moderate-to-severe plaque psoriasis. Methods: We conducted a multicenter retrospective study in 11 Italian Dermatology Units. The effectiveness of the drugs was evaluated by assessing the percentage of patients achieving HS Clinical Response (HiSCR) each week. Results: We enrolled 41 patients with at least 16 weeks of follow-up, with 17 of them completing 52 weeks of treatment. The most commonly prescribed anti-IL drug was secukinumab (27 patients), followed by ixekizumab (5) and guselkumab (5). The HiSCR was achieved by 39%, 74.3%, and 77.8% of patients after 16, 32, and 52 weeks, respectively. No severe adverse events (AEs) or AEs leading to discontinuation were observed during the study. The most common AE was nasopharyngitis (4 patients). Conclusion: In this real-world study, we highlight the effectiveness of anti-IL-23 and anti-IL-17 drugs in the treatment of concomitant plaque psoriasis and severe HS. Longer and larger studies are needed to further evaluate the long-term effectiveness and safety of these treatments in patients affected by HS.